Evaluating the Role of Interactive Encouragement Prompts for Parents in Parent–Child Stress Management - Pinhao Wang; Lening Huang; Guang Dai; Jing Li; Jun Hu; Emilia Barakova; Cheng Yao; Fangtian Ying (Applied Sciences)
Parental involvement is crucial for children’s stress management, and co-regulation of stress can have a positive effect. To facilitate parental involvement in children’s stress management in learning, we proposed an embodied connected system, which provides stress detection, stress information feedback, and encouragement prompts, aiming to help parents better understand and engage in children’s stress-regulation process. This article focuses on the impact of interactive encouragement prompts provided to parents on children’s stress management. The within-group experiment was used to collect stress data and scales from 36 parent–child groups during a controlled learning experiment, and semi-structured interviews were conducted with parents and children. The results indicate that the encouragement prompts provided to the parents enhance the effectiveness of stress relief in children facilitated by parental involvement. In particular, the psychological stress was reduced, and the communication between parents and children became more effective. In addition, active parental involvement and timely encouragement prompts can improve children’s stress-coping abilities, providing an interactive intervention approach for learning stress management.